ONLINE COURSE REGISTRATION - THUY, NGUYEN THIXUAN (Universiti Teknologi Petronas, 2006)
Currently, Information Technology has been developing in Viet Nam and it now has been openly applied to support education system. But in Viet Nam, most of the University have not built their own webpage except some big University. But the problem is, all the webpage of that University is concern to upload information only and don't have any University use the online system as a link to the website. Especially in University requires highly technology to help administrator to save time and convenience in control the education system. At the moment, all the University in Viet Nam don't have any online course registration. They usually using the paper - based to control the number of students register for the courses. This method takes time and effort for the administration because they can not control exactly how many students in the database and if they want to search for the records of students, they have to find for a long time. By using the online course registration, administration can save time and easily control the students in university that register for the new courses. Because in Viet Nam, they never used the online courses registration before , so based on the UTP online course registration as a reference to build a new system for National University of Hanoi. Since then, all the other university can follow and use it to reduce the works process manually. Beside that, from the current system which UTP is using, a new system will be build to suit with the context of university in Vietnam. It is hoping that, by building this systemwe can apply it to the education system in Viet Nam and will benefit to the social, to the students and university in control the students. This document will cover the background study of the project, problem statement, literature review and methodology is being used to build this project. The main tools need to develop this project is html tool and PHP.